A articulação entre avaliação, ensino e aprendizagem na sala de aula de matemática - Barbosa, Elsa (2022)
Students’ performance in the subject of Mathematics continues to be problematic which, according to investigations, is associated to the persistence of assessment practices almost exclusively driven by rating and disjointed from teaching practices. In this context, the current article aims to analyse the articulation between assessment, teaching and learning processes in a 7th grade Mathematics classroom, in the scope of a wider investigation project. Taking on a holistic vision of the classroom, the design research mode was used to answer an intervention in this context, by means of the implementation of educational resources and assessment, teaching and learning practices, with a consequence in the professional development of the parties involved. Preliminary results suggest articulation episodes between the processes in hand rooted in the link between preparation, action and reflection after classes consistent with the functions of the tasks and their implementation, the definitions of teaching strategies, the systematic use of feedback strategies, self-assessment and assessment among peers, so as to allow students to regulate and self-regulate their learnings